Aggression Toward Teachers and Negative Consequences: The Moderating Effects of Procedural Justice - Moon, Byongook (Victims & offenders, 2023)
Several empirical studies have found that violence against teachers is a highly prevalent phenomenon in schools across the United States and has detrimental negative effects on victimized teachers. However, no empirical research has been conducted to explore the moderating effect of procedural justice on the relationship between victimization and physical/emotional distress. The present research, using a sample of victimized teachers via physical assault and theft/vandalism in a metropolitan region in Texas, investigates whether victimized teachers’ perception of procedural justice can play a significant role in moderating the negative impacts of violence against teachers on victimized teachers’ physical and emotional wellbeing. The results indicate that victimization via theft/vandalism and physical assault is closely related to victimized teachers’ emotional and physical distress. The findings show that the level of procedural justice schools demonstrate when handling teacher victimization incidents is associated with beneficial effects of reducing physical and emotional harm among victimized teachers.